The Influence of Brainstorming Method Through “Good Collaboration” Stories to Improve the Critical Thinking Dimension of Elementary School Students - Barokah Khasanah, Sahrul; Puspita, Yenny; Faipri Selegi, Susanti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Indonesian Language Learning is a learning that has an important role in developing students' critical thinking skills. In fact, the critical thinking ability of students in class IV of SD Negeri 80 Palembang in learning Indonesian is still classified as low. The purpose of this research is to find out the influence of the brainstorming method through the story "Good Cooperation" in improving the critical thinking dimension of students in the learning of Indonesian Language Class IV of State Elementary School 80 Palembang. The research method used is the experimental method of the Pre-Experimental design type with one group pretest-posttest design. The population in this study is all class IV of SD Negeri 80 Palembang as many as 49 students. The sample used is class IV A with 25 students. The data analysis technique used is the paired sample t-test. Based on the calculation results, it was obtained that there was an increase in the average pretest-posttest results of 22.92, with a significant value (2-tailed) of 0.000 < 0.05 then H0 was rejected and Ha was accepted. So it can be concluded that the brainstorming method through the story "Good Cooperation" has an effect in increasing the critical dimension of students in Indonesian Language subjects Class IV of SD Negeri 80 Palembang.